2020
DOI: 10.3390/ani10040564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In Ovo Supplementation with Nanonutrition (L-Arginine Conjugated with Ag NPs) on Muscle Growth, Immune Response and Heat Shock Proteins at Different Chicken Embryonic Development Stages

Abstract: The aim of the study was to analyze the in ovo injection of inorganic and organic synthesized silver nanoparticles (Ag NPs) using Brassica oleracea L. var. capitate F. rubra (BOL) conjugation with L-Arginine (L-Arg) on the immune, muscle growth, survivability and hatchability of broiler chickens. The conjugation of L-Arg (100 μg) with 1000 µg of Ag NPs synthesized by (BOL)-extract and L-Arg (100 μg) conjugated with 100 µg of Ag NPs inorganic synthesized were injected into fertile eggs at 8 d, 14 d and 18 d of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Taurine, supplemented in ovo to chicken embryos, improved the structure of breast muscle by increasing the expression of PCNA protein [ 6 ]. L-Arginina conjugated with nanoparticles of Ag activates myogenin and MyoD expression, which is pointed to improve muscle growth [ 7 ]. Due to the fact that embryonic development takes more than 1/3 of the life of broiler chickens and is a key period for muscle development, the method of in ovo feeding is very promising [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taurine, supplemented in ovo to chicken embryos, improved the structure of breast muscle by increasing the expression of PCNA protein [ 6 ]. L-Arginina conjugated with nanoparticles of Ag activates myogenin and MyoD expression, which is pointed to improve muscle growth [ 7 ]. Due to the fact that embryonic development takes more than 1/3 of the life of broiler chickens and is a key period for muscle development, the method of in ovo feeding is very promising [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was documented that the expression of myogenin and MyoD was significantly upregulated by IOF of l-arginine (100 μg) on day 14 of incubation (Subramaniyan et al 2019). Likewise, Subramaniyan et al (2020) confirmed that IOF of l-arginine conjugated with silver nanoparticles (100 μg with 1 000 µg, respectively) on day 14 of incubation upregulated the protein expression of muscle development markers (myogenin and myoD). Also, Gonzales et al (2022) detected that IOF of 0.150 mg folic acid increased the expression of the Pax7 and Myf genes involved in satellite cell proliferation in the pectoralis muscle of hatched chicks.…”
Section: Impact Of In Ovo Feeding Of Nutraceuticals On Growth Perform...mentioning
confidence: 59%
“…Similarly, Gonzales et al (2022) revealed that IOF with a combination of sulphur amino acids (5.90 mg of l-methionine and 3.40 mg of l-cysteine) plus 0.150 mg of folic acid increased the relative weights of thymus and spleen at 21 days of age. Moreover, it was demonstrated that IOF of 100 μg l-arginine (Subramaniyan et al 2019) or 100 μg l-arginine conjugated with 1 000 µg silver nanoparticles (Subramaniyan et al 2020) on day 14 of incubation increased the serum concentration of IgM in newly hatched chicks. In the same line, Kermanshahi et al (2017) stated that IOF of 0.5 mg threonine on day 11 of embryogenesis upregulated IgA mRNA in the new-born chicks of Japanese quail.…”
Section: Impact Of In Ovo Feeding Of Nutraceuticals On Immune Responsementioning
confidence: 99%
“…Arginine plays a crucial role in the production of polyamine and NO, which are strong anti-stress and vasodilator factors in mammals [2]. In addition, Arg facilitates the provision of cellular signaling, intestinal recovery, and immunity factors [10,14]. Therefore, it can be hypothesized that the use of dietary Arg levels in higher doses than the recommended requirement may decrease the ZnO requirement during the stressful condition.…”
Section: Introductionmentioning
confidence: 99%